GATHUTKACA GANDRUNG: SEBUAH STUDI TENTANG PSIKOLOGI KARAKTER TOKOH DAN BENTUK DALAM TARI GAYA SURAKARTA - Suharji Suharji (Gelar : Jurnal Seni Budaya, 2011)
Gathutkaca Gandrung dance is a single dance that symbolizes character of Gathutkaca who falling in love. Gathutkaca has a jolt caused inner conflict. His behavior presented in this dance full of inner conflict for loved his cousin or took his beloved woman whom have gotten marriage proposal submitted by other. Finally, Gathutkaca understood that he could overcome this  conflict through a assertiveness. The gesture when Gathutkaca Gandrung (falling in love) categorized into three parts: 1) maju beksan; 2) beksan; dan 3) mundur beksan. Gathutkaca Gandrung dance began with music of ada-ada greget, and then Gending Sampak with kendhang opening. The next was suwuk and followed by sendhon tlutur jugag. Beksan categorized into four parts. Parts I began with opening of  Ketawang Kinanthi Pawukir, followed by  ada-ada greget saut wantah. Parts II was musical instrument of Gending Lancaran Bendrong especially ompak. Parts III was Gending Ladrang Pucung Rubuh in rime of dados for merong and ngelik. Parts IV was kiprahan Gending Lancaran Bendrong and then suwuk. Mundur beksan was the last performance which Gending Sampak Laras Slendro pathet Manyura presented be its ending. Keywords :  Gandrung, beksan of dance, Gathutkaca.